Mushroom polysaccharides with potential in anti-diabetes: Biological mechanisms, extraction, and future perspectives: A review - Liu, Xiaofei; Luo, Donghui; Guan, Jingjing; Chen, Jin; Xu, Xiaofei (Frontiers in Nutrition, 2022)
Diabetes mellitus (DM) is a global health threat. Searching for anti-diabetic components from natural resources is of intense interest to scientists. Mushroom polysaccharides have received growing attention in anti-diabetes fields due to their advantages in broad resources, structure diversity, and multiple bioactivities, which are considered an unlimited source of healthy active components potentially applied in functional foods and nutraceuticals. In this review, the current knowledge about the roles of oxidative stress in the pathogenesis of DM, the extraction method of mushroom polysaccharides, and their potential biological mechanisms associated with anti-diabetes, including anti-oxidant, hypolipidemic, anti-inflammatory, and gut microbiota modulatory actions, were summarized based on a variety of in vitro and in vivo studies, with aiming at better understanding the roles of mushroom polysaccharides in the prevention and management of DM and its complications. Finally, future perspectives including bridging the gap between the intervention of mushroom polysaccharides and the modulation of insulin signaling pathway, revealing structure-bioactivity of mushroom polysaccharides, developing synergistic foods, conducting well-controlled clinical trials that may be very helpful in discovering valuable mushroom polysaccharides and better applications of mushroom polysaccharides in diabetic control were proposed.